2000
DOI: 10.1016/s0167-4889(00)00049-5
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of human PLD1 and PLD2 by calcium and protein kinase C

Abstract: Numerous studies show that PLD is activated in cells by calcium and by protein kinase C (PKC). We found that human PLD1 and PLD2 expressed in Sf9 cells can be activated by calcium-mobilizing agonists and by co-expression with PKCalpha. The calcium-mobilizing agonists A23187 and CryIC toxin triggered large increases in phosphatidylethanol (PtdEth) production in Sf9 cells over-expressing PLD1 and PLD2, but not in vector controls. PLD activation by these agonists was largely dependent on extracellular calcium. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
38
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 40 publications
6
38
0
2
Order By: Relevance
“…6A). Consistent with our results, Siddiqi et al (19) demonstrate that in Sf9 cells, where both PKC␣ and PKC␦ expression are undetectable, PMA barely activated PLD2. However, overexpression of PKC␣, but not PKC␦, significantly enhanced both basal and PMA-stimulated PLD2 activity.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…6A). Consistent with our results, Siddiqi et al (19) demonstrate that in Sf9 cells, where both PKC␣ and PKC␦ expression are undetectable, PMA barely activated PLD2. However, overexpression of PKC␣, but not PKC␦, significantly enhanced both basal and PMA-stimulated PLD2 activity.…”
Section: Discussionsupporting
confidence: 93%
“…The present results show that PMA stimulates PLD2 activity up to 6-fold when overexpressed in COS-7 cells (Fig. 1), in contrast to a previous report (11) but in agreement with studies in HEK293 and Sf9 cells, where PLD2 also showed large responses to PMA or PKC␣ when overexpressed (19,30).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations